2016
DOI: 10.18805/ijare.v50i2.9589
|View full text |Cite
|
Sign up to set email alerts
|

Screening of pigeonpea genotypes against wilt and sterility mosaic disease in Telangana state, India

Abstract: The pigeonpea germplasms/genotypes were evaluated to identify the sources of resistance to <italic>Fusarium</italic> wilt and sterility mosaic disease. Screening of 55 AICRP Pigeonpea entries with a check and six Warangal (AVT and PVT) pigeonpea entries was done under wilt sick plot and SMD sick plot during <italic>Kharif</italic>-2013 at RARS, Warangal, Telangana state, India. A total of 52 AICRP pigeonpea entries along with check were also screened against sterility mosaic disease. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…These cultivars clustered at the origin in the AMMI2 biplot. The stable performance of ICP9174 and ICP8863 as resistant checks, as well as ICP2376 and BAHAR as susceptible checks, has been previously reported by Reddy and colleagues [11,24,55]. In the GGE biplot view of the pathogenicity test, it was apparent that BDN-2 was the ideal cultivar for HD studies, and all the Fusarium isolates were effective in causing disease in the ICP2376 and BAHAR HDs.…”
Section: Discussionsupporting
confidence: 59%
“…These cultivars clustered at the origin in the AMMI2 biplot. The stable performance of ICP9174 and ICP8863 as resistant checks, as well as ICP2376 and BAHAR as susceptible checks, has been previously reported by Reddy and colleagues [11,24,55]. In the GGE biplot view of the pathogenicity test, it was apparent that BDN-2 was the ideal cultivar for HD studies, and all the Fusarium isolates were effective in causing disease in the ICP2376 and BAHAR HDs.…”
Section: Discussionsupporting
confidence: 59%
“…A similar kind of results was reported in earlier studies where 52 AICRP Pigeonpea genotypes and checks were screened for SMD, and out of that, only eight entries viz. ICPL-87119, ICPL-2376, BDN-2, PT-4-307, CORG-9701, BSMR-736, GRG-811, and BSMR-853 were resistant entries (Bhaskar, 2016). In the past study, 61 Hyderabad accessions were tested against SMD, only two entries viz.…”
Section: Identification Of Resistant Genotypesmentioning
confidence: 97%
“…Dipshikha Kaushik et al [12] found a negative link between mite population and heavy rainfall because it prevents mites from multiplying quickly. Furthermore, Vijaya Bhaskar [13], Roy Abhay Nath, and Kumar Birendra [14] discovered three resistant genotypes and twelve moderately resistant genotypes to sterility mosaic disease against the tick variety.…”
Section: Per Cent Smd Incidencementioning
confidence: 99%